Effects of IL-38 on Macrophages and Myocardial Ischemic Injury - Li, Zhiyang; Ding, Yan; Peng, Yudong; Yu, Jian; Pan, Chengliang; Cai, Yifan; Dong, Qian; Zhong, Yucheng; Zhu, Ruirui; Yu, Kunwu; Zeng, Qiutang (Frontiers in Immunology, 2022)
Macrophages play an important role in clearing necrotic myocardial tissues, myocardial ischemia-reperfusion injury, and ventricular remodeling after myocardial infarction). M1 macrophages not only participate in the inflammatory response in the myocardial tissues after infarction, which causes heart damage, but also exert a protective effect on the heart during ischemia. In contrast, M2 macrophages exhibit anti-inflammatory and tissue repair properties by inducing the production of high levels of anti-inflammatory cytokines and fibro-progenitor cells. Interleukin (IL)-38, a new member of the IL-1 family, has been reported to modulate the IL-36 signaling pathway by playing a role similar to that of the IL-36 receptor antagonist, which also affects the production and secretion of macrophage-related inflammatory factors that play an anti-inflammatory role. IL-38 can relieve myocardial ischemia-reperfusion injury by promoting the differentiation of M1 macrophages into M2 macrophages, inhibit the activation of NLPR3 inflammasome and increase the secretion of anti-inflammatory cytokines, such as IL-10 and transforming growth factor-β. The intact recombinant IL-38 can also bind to IL-1RAPL1 to activate the JNK/AP1 pathway and increase the production of IL-6. In addition, IL-38 regulates dendritic cell-induced cardiac regulatory T-cells, thereby regulating macrophage polarization and improving ventricular remodeling after myocardial infarction. Accordingly, we speculated that IL-38 and macrophage regulation may be therapeutic targets for ameliorating myocardial ischemic injury and ventricular remodeling after myocardial infarction. However, the specific mechanism of IL-38 action warrants further investigation.